MRI-guided dual-responsive anti-tumor nanostructures for synergistic chemo-photothermal therapy and chemodynamic therapy. (1st March 2023) - Shi, Yupeng; Zhou, Mengyang; Zhang, Yong; Wang, Yifei; Cheng, Jingliang
Abstract: Image-guided stimulus-responsive theranostics are beneficial for identifying malignant lesions and integrating multiple cell-killing mechanisms to enhance tumor cell clearance. Herein, an intelligent dual-responsive nanostructure (HSPMH-DOX) was developed for magnetic resonance imaging (MRI)-guided synergistic chemo-photothermal therapy (PTT) and chemodynamic therapy (CDT). The core-shell nanostructure was synthesized by layering polydopamine (PDA), manganese oxide (MnO2 ), and hyaluronic acid (HA) onto drug-loaded hollow mesoporous silica nanoparticles (HS). The constructed nanoagent has both endogenous and external dual responses. The tumor microenvironment (pH/GSH) can trigger the degradation of gatekeeper (MnO2 and PDA), resulting in the release of anti-tumor drugs, whereas external near-infrared light irradiation can accelerate the degradation process and generate local overheating, resulting in PTT. Notably, MnO2 can not only consume intracellular GSH to enhance CDT but also release Mn 2+ for precise localization of tumor tissues using MRI. Both in vitro and in vivo experiments showed that the prepared dual-response nanoagent satisfied biocompatibility, targeting, and the great efficiency of MRI-guided combined therapy. In animal models, combining chemo-PTT and CDT can eradicate tumors in less than two weeks. This work could pave the way for a wide range of stimulus-responsive synergistic theranostic applications, including MRI, chemo-photothermal therapy, and chemodynmic therapy. Statement of significance: Low bioavailability and severe side effects remain the major limitations of conventional cancer chemotherapy. Image-guided combination therapy can alleviate these problems and improve tumor-specific therapy. In the present study, the anticancer drug doxorubicin was encapsulated in a core-shell hollow mesoporous silica nanostructure (HSPMH-DOX), enabling MRI-guided targeted release under both endogenous and external dual stimuli. Moreover, the photothermal and nanoenzymatic effects of nanomedicine can cause local overheating in the tumor and amplify the intracellular CDT effect, accelerating tumor eradication. Systematic evaluations in vitro and in vivo confirmed that nanomedicine enables highly effective MRI-guided synergistic chemo-photothermal and chemodynamic therapy. This work offers a promising therapeutic strategy for precise anti-tumor applications. Graphical abstract: Image, graphical abstract